Tawaran Model KKR Indonesia Dalam Penyelesaian Pelanggaran Ham Berat Masa Lalu Dengan Sejumlah Pengalaman Pembanding - Rian Adhivira Prabowo; Kukuh Budi Mulya (Soegijapranata Catholic University, 2021)
: How a nation contront it’s past is one of the topics on studies of transititonal justice. Since Constitutional Court nullified Indonesian TRC Law 27/2004, reconciliation in Indonesia has entered a status quo. This paper explores possibilities on regulating the future of Indonesian reconciliation law based on three points of departures: (i) the dynamics on regulating reconciliation in Indonesia, (ii) precedents from Constitutional Court’s decisions, and (iii) lesson learned from South Africa and Chile’s TRCs. Using normative legal approach, this paper proposes four reconciliation models: (i) legal policy with amnesy, (ii) legal policy without amnesty, (iii) political policy, and (iv) an alternative model with the formation of Reparation Commission. This paper concludes the last offered model as the least resort for fulfilling victims’ rights on reparation while anticipating future legal/political policy on reconciliation.